Trisomy 8 in pediatric acute myeloid leukemia: A NOPHO‐AML study. Issue 9 (23rd June 2016) - Laursen, Anne Cathrine Lund; Sandahl, Julie Damgaard; Kjeldsen, Eigil; Abrahamsson, Jonas; Asdahl, Peter; Ha, Shau‐Yin; Heldrup, Jesper; Jahnukainen, Kirsi; Jónsson, Ólafur G.; Lausen, Birgitte; Palle, Josefine; Zeller, Bernward; et al.
Abstract : Trisomy 8 (+8) is a common cytogenetic aberration in acute myeloid leukemia (AML); however, the impact of +8 in pediatric AML is largely unknown. We retrospectively investigated 609 patients from the NOPHO‐AML database to determine the clinical and cytogenetic characteristics of +8 in pediatric AML and to investigate its prognostic impact. Complete cytogenetic data were available in 596 patients (98%) aged 0–18 years, diagnosed from 1993 to 2012, and treated according to the NOPHO‐AML 1993 and 2004 protocols in the Nordic countries and Hong Kong. We identified 86 patients (14%) with +8. Trisomy 8 was combined with other cytogenetic aberrations in 68 patients (11%) (+8 other ) and in 18 patients (3%), it was the sole abnormality (+8 alone). Trisomy 8 was associated with FAB M5 (36%) but otherwise clinically comparable with non‐trisomy 8 patients. Trisomy 8 was favorable in patients of young age and with t(9;11). Trisomy 8 alone was associated with older age (median age 10.1 years), FAB M2 (33%), and FLT3 ‐ITD mutations (58%). The 5‐year event‐free survival for patients with +8 alone was 50% and 5‐year overall survival was 75%. In conclusion, +8 is one of the most common cytogenetic aberrations in pediatric AML. Trisomy 8 positive AML is a heterogeneous group and the majority of cases have additional cytogenetic aberrations. Patients with +8 alone differed from patients with +8 other and were associated with older age, FAB M2, and FLT3 ‐ITD aberrations. There were no differences in survival despite the more frequent occurrence of FLT3 ‐ITD in +8 alone. © 2016 Wiley Periodicals, Inc.